THE EFFECTIVENESS OF FIX-UP STRATEGY IN TEACHING READING SKILL TO STUDENTS - Safruddin, Munawarah; Mardianah, Mardianah; Awaliah, Indah Miftah (English Language Teaching for EFL Learners Journal, 2020)
The research aimed at finding out the effectiveness of fix-up a strategy in teaching descriptive text with the research objective: To find out the efficacy of fix-up strategy in teaching reading skill to students of MA Darussalam Anrong Appaka Pangkep. This research was conducted at MA Darussalam Anrong Appaka Pangkep in Academic Year 2018/2019. The research findings showed that the second grades students of MA Darussalam Anrong Appaka Pangkep obtained score on pre-test with the mean score 39,28, which classified as poor. After giving treatment, the students obtained improvement, they gained score with the mean score 56,96 as fair classification. The results of the data analysis indicated that there was an improvement in the students reading descriptive text after being taught using fix-up strategy. It was proved by the result of the statistical analysis of the level significance 0.05 with a degree of freedom (df) 48 indicated t-test values of the students’ reading descriptive text (5.382) was higher than t-table value (2.021). Based on the result analysis, the impact of this research on the students of MA Darussalam Anrong Appaka Pangkep can make the students think critically when they read a text because of the students connecting their prior knowledge related to the text. The researcher found that fix-up strategy helps the students understand the text when they get stuck in reading descriptive.